Down and out in Paris and London - Orwell, George, ....-; Orwell, George, ....- (Harmondsworth : Penguin Books, 1979)
Renowned urban artist Shepard Fairey's new look for Orwell's classic account of life on the streets To be poor and destitute in 1920s Paris and London was to experience life at its lowest ebb. George Orwell, penniless and with nowhere to go, found himself experiencing just this as he wandered the streets of both capitals in search of a job. By day, he tramped the streets, often passing time with 'screevers' or street artists, drunks and other hobos. At night, he stood in line for a bed in a 'spike' or doss house, where a cup of sugary tea, a hunk of stale bread and a blanket were the only sustenance and comfort on offer. Down and Out in Paris and London is George Orwell's haunting account of the streets and those who have no choice but to live on them.
Keywords: Fiction